2001
DOI: 10.1002/aic.690470411
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the dynamics of depth filtration of non‐Brownian particles

Abstract: A new simulator for flow of aqueous suspensions and deposition of non-Brownian particles in granular media

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 59 publications
2
24
0
1
Order By: Relevance
“…The degree of enhancement is expected to depend on the magnitude of the local fluid velocity at the interface, which in turn depends on the superficial fluid velocity, the detailed pore structure (accounting for the formed biofilms), and the hydraulic permeability of the biofilms (which in turn depends on geometric parameters at smaller length scales -see Step 5). It should be noted that Burganos et al [11] have shown that the deposition rate in granular porous media increases significantly when fluid flow through the already formed deposits is taken into account (and the increase is more pronounced for more porous depositssee their discussion in p. 889). For these two reasons, fluid flow through and convective mass transfer in the biofilm should be taken into account in the formulation of theoretical models and simulators (these two factors have been neglected in all the previous theoretical works).…”
Section: Critical Parametersmentioning
confidence: 95%
See 2 more Smart Citations
“…The degree of enhancement is expected to depend on the magnitude of the local fluid velocity at the interface, which in turn depends on the superficial fluid velocity, the detailed pore structure (accounting for the formed biofilms), and the hydraulic permeability of the biofilms (which in turn depends on geometric parameters at smaller length scales -see Step 5). It should be noted that Burganos et al [11] have shown that the deposition rate in granular porous media increases significantly when fluid flow through the already formed deposits is taken into account (and the increase is more pronounced for more porous depositssee their discussion in p. 889). For these two reasons, fluid flow through and convective mass transfer in the biofilm should be taken into account in the formulation of theoretical models and simulators (these two factors have been neglected in all the previous theoretical works).…”
Section: Critical Parametersmentioning
confidence: 95%
“…Simulations of the depth filtration of non-Brownian particles (size larger than 2 lm) by Burganos et al [9][10][11] have shown that the fraction of convected-out particles is highly dependent on the detailed pore geometry and the superficial fluid velocity. In particular, the fraction of convected-out particles increases as the superficial velocity and/or the size of the constriction between neighboring grains increase.…”
Section: Critical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors have recognized the potential of network models for understanding filtration processes by directly modeling the pore scale flow of particle suspensions (Rege and Fogler, 1988;Imdakm and Sahimi, 1991;Datta and Redner, 1998a, b;Lee and Koplik, 2001). For example, Burganos et al (1992Burganos et al ( , 2001 have developed 2-D and 3-D regular lattice models where each link has a constricted tube geometry and particle infiltration is computed using trajectory analyses (after Tien and Payatakes, 1979). In practice, it is often difficult to apply network models due to the limited information usually available for characterizing the pore morphology.…”
Section: Introductionmentioning
confidence: 99%
“…As this work described limiting cases, the authors considered the transient behavior of the filtration process to be a combination of both cases and derived a semi-empirical correlation depending on operating variables which, in some cases, successfully predicted results from independent sources. More recently, Burganos et al [19] and Skouras et al [20] Furthermore, only a few of these models are truly predictive and they often require time-and memoryconsuming computations of streamlines and particle trajectories. In this article, based on theoretical considerations, we propose a new modeling principle for changes to the pressure drop and filtration efficiency throughout the granular bed during clogging with Brownian aerosols.…”
Section: Introductionmentioning
confidence: 99%